2016
DOI: 10.4336/2016.pfb.36.87.1146
|View full text |Cite
|
Sign up to set email alerts
|

Nutrição e enraizamento adventício de plantas lenhosas

Abstract: O sucesso da propagação vegetativa de genótipos comerciais via técnicas de estaquia está relacionado a diversos fatores, dentre os quais o estado nutricional das plantas matrizes doadoras de propágulos e dos propágulos. O status nutricional determina a quantidade de carboidratos, auxinas e outros compostos do metabolismo essencial da planta para a iniciação e desenvolvimento da rizogênese. Cada nutriente possui na planta funções específicas essenciais, podendo atuar estruturalmente ou fisiologicamente. Contudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…However, adventitious root formation can also occur through xylogenesis, the genetic control of wood formation, and involves the expression of a series of genes with complex molecular regulations that favor xylem diff erentiation into a root primordium (Pereira and Bandeira, 2016). It was found that there was no correlation between cuttings rooting and callus formation, indicating that the adventitious root formation in Azadirachta indica cuttings occurs directly.…”
Section: Adventitious Rooting Dynamicsmentioning
confidence: 99%
“…However, adventitious root formation can also occur through xylogenesis, the genetic control of wood formation, and involves the expression of a series of genes with complex molecular regulations that favor xylem diff erentiation into a root primordium (Pereira and Bandeira, 2016). It was found that there was no correlation between cuttings rooting and callus formation, indicating that the adventitious root formation in Azadirachta indica cuttings occurs directly.…”
Section: Adventitious Rooting Dynamicsmentioning
confidence: 99%
“…The nutritional condition of the collected propagule determines the amount of metabolic compounds, such as carbohydrates and auxins, which are essential to the rhizogenesis initiation and speed (Xavier et al, 2013;Pereira and Peres, 2016;Almeida et al, 2017). According to Dias et al (2012), the more nourished the plant, the greater the number of cells produced by the meristems and the longer the growth axis will be, thus reaching the lower end of the tube in a short time.…”
Section: Radicular System Vigormentioning
confidence: 99%
“…Outras características a serem consideradas e que são de extrema importância para o êxito na produção de mudas via propagação vegetativa é a idade, o estado fitossanitário e nutricional da planta matriz quando esta é doadora de material usado na propagação. Esses fatores, principalmente o estádio nutricional, podem determinar a quantidade de carboidratos, auxinas e outros compostos do metabolismo essencial da planta para a iniciação e desenvolvimento das raízes adventícias (Pereira & Peres, 2016). Sendo assim, é pertinente destacar que estacas com maiores reservas de carboidratos podem apresentar melhores taxas de enraizamento.…”
Section: Introductionunclassified